Cataloguing legal publications - Suja', Balqis (2011)
This is the 2nd day lecture, advanced to the practical stage of cataloguing, outlined with topics as: AACR2R and LCRI rules applied to legal publications; Cataloguing the compiled statutes; Basics of serials / integrating resources cataloguing; Subject analysis, and; Introduction to LCC Scheme class K